Pelatihan Pemetaan Geologi Menggunakan Metode Lintasan Tali Kompas Di SMA Negeri 1 Kabupaten Ketapang - Sartika, Sartika; Aqla, Syarifah; Herman, Herman; Firman, Firman (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
SMAN 1 Ketapang often win in regional to provincial level olympiads including physics, earth, astronomy, and geography. In supporting the achievements that have been achieved, Polytechnic State of Ketapang can contribute in terms of sharing knowledge about geography such as geological mapping using compass traverse. Compass traverse are generally used in regional geological mapping to measure, and describe rock units which are converted into mapping space. This mapping activity requires equipment such as a geological compass, which has not accommodated at school. Based on the analysis of the situation, the problems need to be solved by training in geological mapping using the compass traverse method as the implementation of geography lessons. The implementation of training activities is carried out by theory and field practice. The achievement of training objectives can be measured based on several achievement indicators such as the introduction of geological and topographic maps, training in the use of geological compasses and GPS, the practice of mapping compass traverse and processing compass traverse data. The results of the evaluation of the overall activity measurement of all indicators can be assessed as good with an average value of 76.75%.